Wild Planet Toys and e-commerce : when should a manufacturer become an e-tailer? - Glazer, Rashi; Levine, Karen; Katz, David; Zelmar, Karen (London : SAGE Publications Ltd, 2017)
Since it was founded in 1993, Wild Planet Toys has created a distinctive identity in the highly competitive toy industry. The firm designs and manufactures toys for boys and girls ages 4 to 11 and has earned the loyalty of parents through its commitment to fun, educational, non-violent, and non-gender-specific toys. Wild Planet recognizes that its current web site has major shortcomings and is preparing to overhaul the site. But these preparations have raised an important question. Should Wild Planet sell its products through its site? And if so, how? What will the site contain, who will it be targeted to and how will orders be fulfilled? And how will Wild Planets existing retailers react to the firm selling direct?
Originally published in Glazer, R., Levine, K., Katz, D., & Zelmar, K. (2007). Wild Planet Toys and e-commerce: When should a manufacturer become an e-tailer? The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Wild Planet Toys; Toy industry -- Marketing; Electronic commerce